The Influence of Leadership Style and Work Discipline on Employee Performance with Work Motivation as an Intervening Variable in MSMEs in Sidoarjo Regency - Putri Oktaviana Anjaswangi; Sumartik Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and explain the influence of leadership style, work discipline on employee performance with work motivation as an intervening variable in MSMEs in the village of Sepande, Kec. District Temple. Sidoarjo.. In this study, we will examine the respondents, namely employees of SMEs in the village of Sepande. The method used is quantitative research with a sample of 90 employees. Data collection using a questionnaire using proportional random sampling technique. The data analysis used is the outer model test and the inner model test on the Smart PLS software application. The results of this study indicate that the Leadership Style, Work Discipline, Work Motivation on MSMEs in the village of Sepande, Kec. District Temple. Sidoarjo has a direct effect on employee performance.